Improving Students’ Arabic Vocabulary at MTsN Batu Through a Project-Based and Mind Mapping Approach - Rahmadani, Rahmadani; Daroini, Slamet; Solihah, Mamluatu (Abjadia : International Journal of Education, 2025)
This study investigates the effectiveness of integrating the Project-Based Learning (PjBL) model with mind mapping techniques in improving students' mastery of Arabic vocabulary at MTsN Batu. Employing a quantitative approach with a quasi-experimental design, the research involved two distinct groups: an experimental class and a control class. Vocabulary assessments were conducted both prior to and following the intervention. The findings revealed that students exposed to the PjBL and mind mapping approach showed a notable increase in performance, with their average vocabulary scores rising from 50.17 (pre-test) to 81.67 (post-test). An independent samples t-test produced a p-value of 0.001, confirming a statistically significant difference between the two groups. The results indicate that the use of project-based tasks supported by visual tools like mind maps effectively enhances vocabulary acquisition. Additionally, the strategy promotes greater learner engagement, autonomy, and creativity, offering a promising alternative to traditional lecture-based instruction.